The Association Between Fat Free Mass and Basal Metabolic Rate with Handgrip Strength in Female Medical Students - Noor Az Zhahra; Mila Citrawati; Sri Wahyuningsih; Maria Selvester Thadeus (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Handgrip strength is an indicator of general muscle strength. Low handgrip strength is associated with various diseases that can increase morbidity and mortality. Fat free mass and basal metabolic rate are indicators of health and physical fitness. Low physical activity and degenerative changes in muscle strength in female medical students may be risk factors for cardiovascular disease, metabolic syndrome, and sarcopenia in old age. The aim of this study was to determine the association between fat free mass and basal metabolic rate with handgrip strength in female medical students. The type of research includes observational analytics with a cross-sectional design on 54 samples selected using purposive sampling techniques. Fat free mass and basal metabolic rate data were collected using a bioelectrical impedance analysis tool, handgrip strength using a handgrip dynamometry tool which was carried out directly. Statistical data analysis used the Independent sample t-test and Chi-square test. The results of the analysis using the Independent sample t-test found that there was no significant difference based on fat free mass between respondents with low handgrip strength and normal handgrip strength (p = 0.662) and there was a significant association between basal metabolic rate and handgrip strength (p = 0.001) with an odds ratio (OR) of 16.875. Female medical students need to maintain activity performance, train muscle strength, and adopt a healthy lifestyle so that handgrip strength, fat-free mass, and basal metabolic rate are maintained.